A Chewing Study of Abuse-Deterrent Tablets Containing Polyethylene Oxide Using a Robotic Simulator - Chen, Bangxiang; Zhang, Feng; Dhupia, Jaspreet; Morgenstern, Marco P.; Costello, Mark; Boyce, Heather; Sun, Wei-Jhe; Raofi, Saeid; Tian, Li; Xu, Weiliang (AAPS PharmSciTech, 2023)
Abuse-deterrent formulations (ADFs) refer to formulation technologies aiming to deter the abuse of prescription drugs by making the dosage forms difficult to manipulate or extract the opioids. Assessments are required to evaluate the performance of the drugs through different routes including injection, ingestion, and insufflation and also when the drugs are manipulated. Chewing is the easiest and most convenient way to manipulate the drugs and deserves investigation. Chewing is one of the most complex bioprocesses, where the ingested materials are subject to periodic tooth crushing, mixed through the tongue, and lubricated and softened by the saliva. Inter- and intra-subject variations in chewing patterns may result in different chewing performances. The purpose of this study is to use a chewing simulator to assess the deterrent properties of tablets made of polyethylene oxide (PEO). The simulator can mimic human molar grinding with variable chewing parameters including molar trajectory, chewing frequency, and saliva flow rate. To investigate the effects of these parameters, the sizes of the chewed tablet particles and the chewing force were measured to evaluate the chewing performance. Thirty-four out of forty tablets were broken into pieces. The results suggested that the simulator can chew the tablets into smaller particles and that the molar trajectory and saliva flow rate had significant effect on reducing the size of the particles by analysis of variance (ANOVA) while the effect of chewing frequency was not clear. Additionally, chewing force can work as an indicator of the chewing performance.